2021
DOI: 10.32677/ijch.v8i8.2988
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparities in prevalence of obesity among school-aged children in Egypt: A country case study from The Eastern Mediterranean Region

Abstract: Background: This study is a review of recent research conducted in Egypt on the problem of rising prevalence rates of obesity among school-aged children. Methods: The search was conducted in three phases. The key words used were obesity, overweight, school-aged children, and nutritional status specifically for Egyptians over the past decade (2010–2021). Online research sites and the libraries of the Egyptian universities of the eluc.org. websites were searched along with on-site visits to the libraries of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The current study, nutritional status showed the fact that the total prevalence of obesity was 4.2% in preschool children (2-5 years old) in Kaluibiya Governorate in Egypt, while 3.6% were underweight, 15.4% were overweight and 47.1% were stunted. In Egypt a systemic review and meta-analysis study from 24 studies in Egypt; Al-Jawaldeh and Abul-Fadl [20] found that obesity was more common (10.6%) among school-aged youngsters. In the USA affiliated the prevalence rate is progressively rising from 10% at 2 years to 23% at 8 years [21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study, nutritional status showed the fact that the total prevalence of obesity was 4.2% in preschool children (2-5 years old) in Kaluibiya Governorate in Egypt, while 3.6% were underweight, 15.4% were overweight and 47.1% were stunted. In Egypt a systemic review and meta-analysis study from 24 studies in Egypt; Al-Jawaldeh and Abul-Fadl [20] found that obesity was more common (10.6%) among school-aged youngsters. In the USA affiliated the prevalence rate is progressively rising from 10% at 2 years to 23% at 8 years [21] .…”
Section: Discussionmentioning
confidence: 99%
“…There was very little difference in overweight and obesity with increased duration of breastfeeding. Al-Jawaldeh and Abul-Fadl [20] conducted a metanalysis study for preschool children and compared nutritional status of children aged 6-59 months among formula versus exclusively breastfed infants (EBF). They reported that comparing IFM and EBF revealed that, respectively, overweight was 5.4% compared 3.45%, obesity was 13.8% versus 5.65%, stunting was 21.6% versus 1.15, and wasting was 9.7% versus 0.85%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt, studies have shown varied asthma prevalence rates among children. Specifically, a 4.8% prevalence rate was identified in infants and children under four years of age from five different governorates [28]. Another study from El Menoufiya Governorate showed that the prevalence of asthma among primary school children was 6.5% [29].…”
Section: Introductionmentioning
confidence: 97%